The Influence of Principal Leadership on The Quality of Islamic Education - Mohamad Kamil Salas; Masluhah Masluhah (Jurnal Ilmiah Edukatif, 2024)
This study aims to analyze the influence of principal leadership on the quality of Islamic education. Principals have a key role in determining the direction, strategy, and policies that have an impact on the success of educational establishments, particularly in regard to Islamic education that emphasizes moral, spiritual, and academic values. Effective leadership can create a conducive learning environment, motivate educators, and optimize student performance. A quantitative survey with several principals, teachers, and students is the research method employed from various Islamic schools. Data were analyzed using regression techniques to see the correlation between principal leadership variables and the quality of education. The results of the study indicate that participatory, inspiring, and adaptive principal leadership significantly improves the quality of Islamic education, as evidenced by rising academic achievement, the growth of religious character, and high teacher satisfaction. This study emphasizes how crucial it is to give principals more leadership skills in order to raise the standard of Islamic education in Indonesia.